Enhancing Computational Thinking and Learning Engagement through STEM-based Water Turbine Project - Diana Maulidia; Nanang Winarno; Lilik Hasanah; Mutiara Syifa (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
In today’s digital era, students face challenges in developing critical thinking and problem-solving skills essential for success in an increasingly complex world. Computational Thinking (CT) has emerged as a pivotal 21st-century skill for innovation and problem-solving. This study investigates the impact of STEM-based learning through a water turbine project on students’ CT and Learning Engagement (LE) at the secondary school level. A quasi-experimental approach with a pretest-posttest control group design was employed. The participants were 76 of 445 8th-grade students from secondary schools in Bandung, Indonesia, divided equally into experimental and control groups, each comprising 38 students. Statistical analyses using the Mann-Whitney U test on n-gain scores revealed a significant improvement in CT for the experimental group compared to the control group (U = 50.00, sig.). < 0.001, and a large effect size (r = 0.80). Similarly, LE in the experimental group increased significantly compared to the control group (U = 10.50, sig.). < 0.001, and a large effect size (r = 0.85). These results highlight that STEM learning through the water turbine project effectively enhances students’ CT and LE. This study demonstrates the potential of STEM-based approaches to foster essential 21st-century skills among secondary school students. However, further research is needed to explore its application across diverse contexts and skill areas.